PERAN INTELLECTUAL CAPITAL DAN INNOVATIVE BEHAVIOR UNTUK MENINGKATKAN OPPORTUNITY CAPTURE PADA INDUSTRI PERHOTELAN - Wahyudi Henky Soeparto; Thomas Stefanus Kaihatu (Fokus Ekonomi : Jurnal Ilmiah Ekonomi, 2020)
The tourism business in the city of Surabaya, especially the hotel industry, has been hit badly by the Covid-19 pandemic where hotel occupancy rates fell to their lowest level. However, efforts must be made to keep the wheels of the organization running in the face of this difficult situation. Therefore, hotel business actors must make something innovative so that hotels can continue to operate and have a competitive edge. This study attempts to analyze the factors that can generate the ability to opportunity capture through the implementation of innovative behavior which in turn is also driven by various types of intellectual capital at each organizational level such as human capital, organizational capital and social capital. This research is a quantitative study and uses the Generalized Structured Component Analysis (GSCA) method to process research data that has been collected from 74 hotels in the city of Surabaya. Of the four hypotheses developed in this study, only three hypotheses can be accepted, namely human capital has a positive effect on innovative behavior, social capital has a positive effect on innovative behavior, and innovative behavior has a positive effect on opportunity capture. While the hypothesis which states that organizational capital has a positive effect on innovative behavior is not proven.